Carriage of Staphylococcus pseudintermedius by clinically normal dogs in Canterbury, New Zealand. Issue 1 (2nd January 2023) - Wilkinson, DA; Rogers, LE; Bell, A; Benschop, J; Midwinter, AC
ABSTRACT: Aims: To investigate the frequency of carriage of methicillin-susceptible and methicillin-resistant Staphylococcus pseudintermedius (MRSP) in a population of clinically normal dogs within the Christchurch and wider Canterbury region, an area in which MRSP has been detected. Methods: Buccal and perianal swabs were collected from 126 clinically normal dogs presenting at veterinary clinics in the Christchurch/Canterbury region for de-sexing or routine vaccination. S. pseudintermedius was isolated by selective culture. Isolates were tested for susceptibility to 12 antimicrobials by disc diffusion. Results: S. pseudintermedius was isolated from 92/126 (73.0 (95% CI = 64.4–80.5)%) dogs, with 38/126 (30.2 (95% CI = 22.3–39.0)%) positive dogs carrying S. pseudintermedius at both sampled sites. More animals (78/126; 61.9 (95% CI = 52.8–70.4)%) had positive mouth cultures than positive perianal region cultures (52/126; 41.3 (95% CI = 32.6–50.4)%). No MRSP was isolated from clinically normal dogs. However, resistance to penicillin (106/130 (85.1%) swabs) and tetracycline (33/130 (25.4%) swabs) was seen. Conclusions: The majority of the dogs in this sample were carriers of S. pseudintermedius . However, none of these isolates were MRSP. Clinical relevance: While most clinically normal dogs in the studied region are likely to be carriers of S. pseudintermedius, only a small proportion, if any, are likely to be carriers of MRSP. Antibiotic stewardship practices may be important to maintain low-level circulation of drug-resistant bacterial lineages.